HUBUNGAN POLA MAKAN DENGAN KEJADIAN STROKE NON HEMORAGIK DI IRINA F NEUROLOGI RSUP. PROF. DR. R. D. KANDOU MANADO - Maukar, Magreysti; Ismanto, Amatus Yudi; Kundre, Rina (JURNAL KEPERAWATAN, 2014)
Abstract introduction Non â€“ haemorrhagic stroke is a clinical syndrome that appears suddenly, quickly, such as neurologic deficit for lasting 24 hours or more. Risk factors that may cause the occurrence of stroke is hypertension, unhealthy diet, smoking, obesity. The purpose of this study was to analyze the correlation between the diet and the non - haemorrhagic stroke. This research design is using an observational analytic study. According to this research, this research is a cross-sectional study with sample size of 30 respondents. The analysis results of chi square test with values Ï 0.042, so it shows there is a correlation between diet and non â€“ haemorragic stroke incidents. Recommended for the patient or the patient's family is to consume balanced nutrition so that can lowers the incidence of non-hemorrhagic stroke. Keywords: diet, non - haemorrhagic stroke incidence. Abstrak: Pendahuluan Stroke non hemoragik merupakan sindroma klinis yang timbul mendadak, cepat, berupa defisit neurologis yang berlangsung 24 jam atau lebih. Faktor resiko terjadinya stroke yaitu hipertensi, diet yang tidak sehat, merokok dll. Tujuan penelitian ini adalah untuk mengetahui hubungan pola makan dengan kejadian stroke non hemoragik. Desain yang digunakan adalah analitik observasional. penelitian ini bersifat cross sectional study dengan besaran sampel 30 responden. Hasil uji chi square Ï 0,042. Rekomendasi diedukasi kepada pasien atau keluarga pasien untuk mengkonsumsi makanan dengan gizi seimbang sehingga menurunkan angka kejadian stroke non hemoragik. Kata kunci : pola makan, stroke non hemoragik.